2011
DOI: 10.2166/ws.2011.045
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed corona discharge for degradation of aqueous humic substances

Abstract: The research into oxidation of aqueous humic substances (HS) with pulsed corona discharge (PCD) was undertaken to estimate the energy efficiency of the treatment. The PCD system consists of a voltage pulse generator and reactor, in which the gas-phase discharge generating OH radicals and ozone treats the water showered between electrodes. The influence of HS initial concentration, pulse repetition frequency, water flow rate, and the atmosphere composition was evaluated by the decrease in total organic carbon (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…The gas-phase discharges most efficient in water treatment are dielectric barrier and corona discharges, giving high outcomes of active oxygen-based oxidants (Kornev et al 2006;Panorel et al 2011;Pokryvailo et al 2006;Samoilovich et al 1997). "Thermal" spark and arc discharges, seldom applied for water treatment, are characterized with high, up to 10,000 • C, temperature in the discharge channel and may be used for the initiation of high-temperature reactions and emission of UV-radiation.…”
Section: Pulsed Electric Dischargesmentioning
confidence: 99%
See 2 more Smart Citations
“…The gas-phase discharges most efficient in water treatment are dielectric barrier and corona discharges, giving high outcomes of active oxygen-based oxidants (Kornev et al 2006;Panorel et al 2011;Pokryvailo et al 2006;Samoilovich et al 1997). "Thermal" spark and arc discharges, seldom applied for water treatment, are characterized with high, up to 10,000 • C, temperature in the discharge channel and may be used for the initiation of high-temperature reactions and emission of UV-radiation.…”
Section: Pulsed Electric Dischargesmentioning
confidence: 99%
“…The described PCD treatment method showed the energy efficiency at least 2.2 times exceeding the one of traditional ozonation when applied to humic substances oxidation (Panorel et al 2011). Also, the advantage of PCD treatment is relatively simple design of the equipment: the discharge is insensitive towards the gas humidity; the reactor is a closed compartment in which the treatment takes place making the gas transport and the residual ozone destruction unnecessary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results have been reported by Gao et al [39] for the degradation of 17b-estradiol in water by DBD. Panorel et al [32] also reported similar increases in the reaction rates for pulsed corona treatment of aqueous humic acid. The effect of the initial concentration of humic acid solution on the degradation efficiency is presented in Fig.…”
Section: Ha Degradation Kinetic Studymentioning
confidence: 68%
“…It is known that dielectric barrier discharge (DBD) plasma initiates several physical processes (UV light, shock waves) and chemical processes (O , O 3 , H 2 O 2 ) [29], processes which may directly or indirectly act on humic substances. However, limited studies investigate the potential of atmospheric plasma for the breakdown of THMs [30] and HA [31,32]. It is also important to understand the potential for the formation of DBPs after plasma treatment of humic substances to demonstrate the technology's suitability for water treatment.…”
Section: Introductionmentioning
confidence: 99%